Knowledge, Attitude, And Practices On Infection Control During Dental Missions of Dentists Of A Philippine Dental Association Dental Chapter In Metro Manila/Abiel Grace G. Sales. - Sales, Abiel Grace G. Author
INTRODUCTION: In the Philippines, dental missions give dental care and instruction to unreached areas. In dental missions, infections control may not be as good as it is in a dental clinic because of the nontraditional setting. This study examines dentists' knowledge, attitudes, and practices about infection control methods, as well as the form, type, and underlying factors that influence them.